Meningkatkan Kemampuan Membaca Awal Anak Usia 5-6 Tahun Melalui Permainan Hubung Kata di TK Bhakti Pertiwi - Puspita Sandra Dewi Handayani; Melvi Lesmana Alim; Rizki Amalia (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low initial reading ability of children aged 5-6 years at TK Bhakti Pertiwi, Kampar Regency. For this reason, a concrete application is needed to be able to find the right way to relate to children's early reading abilities, namely the application of word connection games. This type of research is classroom action research which is an examination of learning activities in the form of actions, which are deliberately created and occur in a class together with a total of 12 children consisting of 6 boys and 6 girls. . Data collection techniques for data collection in this research are observation and documentation. The data analysis technique used in this research is the percentage technique. From the results of classroom action research and discussions as described, a conclusion was drawn regarding the results of this research, namely that through the application of word connection games, it can improve the early reading skills of children aged 5-6 years at TK Bhakti Pertiwi, Kampar Regency. The early reading ability of children aged 5-6 at TK Bhakti Pertiwi, Kampar Regency through word connection games has increased every cycle. In the pre-cycle, an average score of 39.06% was obtained with the BB (Not Yet Developed) criteria. After improvements were made in cycle I, a score of 57.03% was obtained with MB (Starting to Develop) and in cycle II a score of 78.13% was obtained with BSB (Very Well Developing) criteria. Keywords: Word Connection Games, Early Reading Ability of Children, Aged 5-6 Years.